2022
DOI: 10.3389/fnins.2022.1014948
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating neck circumference or neck-to-height ratio into the GOAL questionnaire to better detect and describe obstructive sleep apnea with application to clinical decisions

Abstract: ObjectiveAlthough neck circumference (NC) and neck-to-height ratio (NHR) have been recognized as effective predictors of the clinical diagnosis of adult obstructive sleep apnea (OSA), they have not been included in the widely used GOAL questionnaire. Not coincidentally, the NHR has not been adequately considered in the development and validation of the STOP-Bang questionnaire, No-Apnea score and the NoSAS score. The motivation for the study was (1) to combine the GOAL questionnaire with the NC and NHR, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
2
0
1
Order By: Relevance
“…These symptoms, in turn, may disturb sleep and reduce its duration. A large NC is a recognized risk factor for obstructive sleep apnea [ 48 , 49 ]. Similar to our results, other studies did not find an association between NC and sleep quality [ 50 , 51 ] due to small sample sizes and other confounding factors [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…These symptoms, in turn, may disturb sleep and reduce its duration. A large NC is a recognized risk factor for obstructive sleep apnea [ 48 , 49 ]. Similar to our results, other studies did not find an association between NC and sleep quality [ 50 , 51 ] due to small sample sizes and other confounding factors [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Âèçíà÷àâñÿ ïîêàçíèê WtHR, ÿê ñï³ââ³äíîøåííÿ îêðóaeíîñò³ òà볿 äî çðîñòó. Îñê³ëüêè âñå á³ëüøå äîñë³äaeåíü âêàçóþòü ïðî âçàºìîçâ'ÿçîê îêðóaeíîñò³ øè¿ (ÎØ) ³ç àïíîå ñíó ó ä³òåé [14,15] -23,8% (n=25), ó áàáö³ ïî ìàìèí³é ë³í³¿ -22,9% (n=24) òà ìàòåð³ -18,1% (n=19). Îaeèð³ííÿ ÷àñò³øå âñüîãî ñïîñòåð³ãàëîñü ó ìàòåð³ -13,3% (n=14) òà áàòüêà -10,5% (n=11).…”
Section: âñòóïunclassified
“…WHtR was calculated as the ratio of waist circumference to height. As a growing number of studies have shown an association between neck circumference (NC) and sleep apnoea in children [14,15], all children with MetS had their NC measured in the supine and standing positions to assess the risk of apnoea. A detailed history and the Epworth Sleepiness Scale for Children and Adolescents (ESS-CHAD) were used to assess subjective daytime sleepiness in relation to sleep disorders such as obstructive sleep apnoea and/or sleep fragmentation.…”
Section: ñLinical Characteristics Of Children and Adolescents With Me...mentioning
confidence: 99%